Hubungan Antara Peer Attchment Dengan FOMO( Fear Of Missing Out) Pada Siswa Kelas X SMA Teuku Umar Semarang - Nanda Hanif Kurnianingsih; Tri Suyati; G. Rohastono Ajie (Journal on Education, 2024)
The aim of this research is to determine the relationship between peer attachment and fear of missing out (FoMO) in class X students at Teuku Umar High School in Semarang. The study found that there was a positive relationship between class X students' peer attachment and their fear of missing out at Teuku Umar High School in Semarang. With 34 students serving as the trial group and 70 students serving as the main research group, this study employed a quantitative correlation method. Using a cluster random selection technique, data was gathered using two measurement scales: the Peer Attachment Scale and the Fear of Missing Out Scale. Three classes were chosen as the trial group and the main research group after all classes were randomly assigned. According to the product moment correlation test results, peer attachment and FOMO in class X SMA Teuku Umar Semarang are positively correlated. This is demonstrated by a rcount of 0.259, which is higher than a rtable of 0.235 at a significance level of 5%. It is hoped that, in light of this research, preventive measures would be taken to heighten class X students' FOMO, which results in excessive worry when they are not aware of the most recent information developments.